Genome-wide association study for early-onset and morbid adult obesity identifies three new risk loci in European populations - Meyre, David; Delplanque, Jérôme; Chèvre, Jean-Claude; Lecoeur, Cécile; Lobbens, Stéphane; Gallina, Sophie; Durand, Emmanuelle; Vatin, Vincent; Degraeve, Franck; Proença, Christine; Gaget, Stefan; Körner, Antje; et al. (Nature genetics, 2009)
Philippe Froguel and colleauges present a genome-wide association study for early-onset and morbid adult obesity, reporting three new genetic associations to obesity. We analyzed genome-wide association data from 1,380 Europeans with early-onset and morbid adult obesity and 1,416 age-matched normal-weight controls. Thirty-eight markers showing strong association were further evaluated in 14,186 European subjects. In addition to FTO and MC4R , we detected significant association of obesity with three new risk loci in NPC1 (endosomal/lysosomal Niemann-Pick C1 gene, P = 2.9 × 10 −7 ), near MAF (encoding the transcription factor c-MAF, P = 3.8 × 10 −13 ) and near PTER (phosphotriesterase-related gene, P = 2.1 × 10 −7 ).